Case reportCancer of the papilla of Vater in which a needle knife precut papillotomy was effective for the pre-operative diagnosis and biliary drainage – report of a case - Naitoh, Itaru; Ohara, Hirotaka; Hayashi, Kazuki; Ogawa, Kanto; Ando, Tomoaki; Nakazawa, Takahiro; Yasuda, Akira; Ochi, Nobuo; Sawai, Hirozumi; Joh, Takashi (Archives of Medical Science, 2008)
The histopathological diagnosis for periampullary tumours is difficult because the accuracy of papillary forceps biopsy is unsatisfactory. Precut papillotomy has recently been performed if endoscopic biliary cannulation is necessary but difficult. Precut papillotomy after placing a pancreatic stent decreases the risk of acute pancreatitis compared to without pancreatic stent. We describe an 80-year-old female with obstructive jaundice caused by cancer of the papilla of Vater. We obtained pre-operative histopathological diagnosis and biliary drainage by needle knife precut papillotomy using a pancreatic stent. Precut papillotomy with pancreatic stent was safe and effective for biliary drainage and pre-operative histopathological evidence.